Probabilistic forecasts for the 2018 FIFA World Cup based on the bookmaker consensus model - Achim Zeileis; Christoph Leitner; Kurt Hornik (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
Football fans worldwide anticipate the 2018 FIFAWorld Cup that will take place in Russia from 14 June to 15 July 2018. 32 of the best teams from 5 confederations compete to determine the new World Champion. Using a consensus model based on quoted odds from 26 bookmakers and betting exchanges a probabilistic forecast for the outcome of the World Cup is obtained. The favorite is Brazil with a forecasted winning probability of 16.6%, closely followed by the defending World Champion and 2017 FIFA Confederations Cup winner Germany with a winning probability of 15.8%. Two other teams also have winning probabilities above 10%: Spain and France with 12.5% and 12.1%, respectively. The results from this bookmaker consensus model are coupled with simulations of the entire tournament to obtain implied abilities for each team. These allow to obtain pairwise probabilities for each possible game along with probabilities for each team to proceed to the various stages of the tournament. This shows that indeed the most likely final is a match of the top favorites Brazil and Germany (with a probability of 5.5%) where Brazil has the chance to compensate the dramatic semifinal in Belo Horizonte, four years ago. However, given that it comes to this final, the chances are almost even (50.6% for Brazil vs. 49.4% for Germany). The most likely semifinals are between the four top teams, i.e., with a probability of 9.4% Brazil and France meet in the first semifinal (with chances slightly in favor of Brazil in such a match, 53.5%) and with 9.2% Germany and Spain play the second semifinal (with chances slightly in favor of Germany with 53.1%). These probabilistic forecasts have been obtained by suitably averaging the quoted winning odds for all teams across bookmakers. More precisely, the odds are first adjusted for the bookmakers' profit margins ("overrounds"), averaged on the log-odds scale, and then transformed back to winning probabilities. Moreover, an "inverse" approach to simulating the tournament yields estimated team abilities (or strengths) from which probabilities for all possible pairwise matches can be derived. This technique (Leitner, Zeileis, and Hornik 2010a) correctly predicted the winner of 2010 FIFAWorld Cup (Leitner, Zeileis, and Hornik 2010b) and three out of four semifinalists at the 2014 FIFAWorld Cup (Zeileis, Leitner, and Hornik 2014).
Keywords: C53; C40; D84; 330; consensus; agreement; bookmakers odds; tournament; 2018 FIFA World Cup